White Crystal Cane Sugar Analysis Using a Noninvasive Method for Detection of Tampering with Sand - Nascimento, Paloma Andrade Martins [UNESP]; Sperança, Marco Aurelio [UNESP]; Romano Beletti, Douglas; Pereira-Filho, Edenir Rodrigues; Pereira, Fabíola Manhas Verbi [UNESP] (Springer Nature, 2021)
In this study, a noninvasive and highly analytical frequency method for the detection of tampering with sand (SA) of white crystal cane sugar (WCCS) was developed using energy-dispersive X-ray fluorescence (EDXRF) combined with chemometric strategies. Sixty-four solid mixture samples with variations in the content of sand were evaluated. The normalization strategy to the unit length (‖b‖) in combination with summed spectral data from EDXRF was applied as a strategy to enhance analytical information. The predicted data using a partial least squares (PLS) model were highly correlated with reference values (R2 = 0.9889), and the standard error of cross-validation (SECV) was 2.7 wt% using two latent variables (LV) corresponding to 97% of the explained variance of the data.
Keywords: Cane sugar; Chemometrics; EDXRF; PLS; Quality assurance; Tampering